STEM Effect In Problem Solving: A Meta Analysis - Arina Novia Dewi; Maryati Maryati; Sabar Nurohman; Suyanta Suyanta; Sri Rejeki Dwi Astuti (Jurnal Penelitian Pendidikan IPA, 2023)
The STEM approach to learning helps prepare students with the skills needed for the future. Concrete and real-world problems can be solved by training students in STEM education. This research aims to analyze the influence of STEM on problem-solving abilities in education. The research method used is meta-analysis. The research process begins with determining the topic, data criteria, article search, data classification, analysis, and conclusion. The topic used is STEM and problem-solving, and the data criteria used are effect sizes. Articles used in the analysis are published in Scopus-indexed journals, ERIC, DOAJ, and SINTA-accredited journals. The articles analyzed are from the years 2018-2023. The result of the study shows that the use of STEM has a significant impact, with an average effect size of 1,709. STEM education has a very large influence on problem-solving abilitie.